Moelleriella sinensis sp. nov. (Clavicipitaceae, Ascomycota) from southeast China - Chen, Yu-Xi; Xue, Qing-Lin; Xie, Yong-Xiao; Keyhani, Nemat O.; Guan, Xia-Yu; Wei, Xiu-Yan; Zhao, Juan; Yan, Zhong; Chen, Hui; Qiu, Jun-Zhi; Guan, Xiong (Phytotaxa, 2020)
Moelleriella sinensis, a fungal pathogen infecting whitefly nymphs (Hemiptera), is described and illustrated as a new species from Wu Yi Mountain in Fujian province, southeastern China. This species is characterized by producing a pale brown spore mass around whitish to pale yellow pulvinate stroma. In surveys of entomopathogenic fungal diversity, only the anamorphic state was found in collected stroma. Phylogenetic analyses using the nucleotide sequences derived from the nuclear ribosomal large subunit rRNA gene, RNA polymerase subunit 1, and translation elongation factor 1α, coupled to morphological characterization supports the placement of the isolate as a new species in a distinct lineage within Moelleriella.